Can AI Predict Cognitive Decline in Elderly Patients? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
The global population is aging at an unprecedented rate, and with this demographic shift comes a growing concern for age-related health issues, particularly ...
Keywords: AI in Neurology; Predict; Cognitive; Decline; Artificial Intelligence; Machine Learning; Deep Learning